2014
DOI: 10.1136/gutjnl-2014-307498
|View full text |Cite
|
Sign up to set email alerts
|

Daclatasvir plus peginterferon alfa and ribavirin for treatment-naive chronic hepatitis C genotype 1 or 4 infection: a randomised study

Abstract: NCT01125189.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
1
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 29 publications
4
79
1
5
Order By: Relevance
“…In the COMMAND-1 trial, 55 treatment-naive HCV GT-1 and 4 patients were treated with DCV (or placebo) plus Peg-IFNa/RBV. The study design consisted of three arms: Peg-IFNa/RBV plus DCV 20 mg, DCV 60 mg, or placebo.…”
Section: Genotypementioning
confidence: 99%
“…In the COMMAND-1 trial, 55 treatment-naive HCV GT-1 and 4 patients were treated with DCV (or placebo) plus Peg-IFNa/RBV. The study design consisted of three arms: Peg-IFNa/RBV plus DCV 20 mg, DCV 60 mg, or placebo.…”
Section: Genotypementioning
confidence: 99%
“…Recently, LDV was shown to inhibit NS5A through direct binding to the NS5A protein, and resistance to LDV was shown to be the result of lower binding affinity to NS5A mutants (12). Targeting NS5A has been validated clinically, as treatment with NS5A inhibitors elicits a rapid decline of HCV viral load (13,14) and enhanced SVR rates when combined with Peg-IFN and RBV (15) or other DAAs, including SOF (7,8,16).…”
mentioning
confidence: 99%
“…An in vitro study revealed that replicons containing multiple NS5A mutations (L28S, M31I, and Y93H) conferred high resistance to DCV [24]. Hézode et al [25] reported treatment failure to DCV in patients infected with genotype 4a mutants harboring double substitutions at positions 28 and 30. In a parallel in vitro study, double substitutions at L28M-R30H and L28M-L30S positions conferred >10,000-fold resistance against the NS5A inhibitors DCV and LDV [25].…”
Section: Ns5a Inhibitorsmentioning
confidence: 99%
“…Hézode et al [25] reported treatment failure to DCV in patients infected with genotype 4a mutants harboring double substitutions at positions 28 and 30. In a parallel in vitro study, double substitutions at L28M-R30H and L28M-L30S positions conferred >10,000-fold resistance against the NS5A inhibitors DCV and LDV [25]. The influence of baseline NS5A single or multiple mutations in genotype 4-infected patients was investigated in 186 patients receiving DCV.…”
Section: Ns5a Inhibitorsmentioning
confidence: 99%